Mitophagy: A key regulator in the pathophysiology and treatment of spinal cord injury - Qiuyang Gu; Shengye Yuan; Yumei An; Wenyue Sun; Mingyuan Xu; Mengchun Xue; Xianzhe Li; Chao Liu; Haiyan Shan; Mingyang Zhang (Neural Regeneration Research)
Mitophagy is closely associated with the pathogenesis of secondary spinal cord injury. Abnormal mitophagy may contribute significantly to secondary spinal cord injury, leading to the impaired production of adenosine triphosphate, ion imbalance, the excessive production of reactive oxygen species, neuroinflammation, and neuronal cell death. Therefore, maintaining an appropriate balance of mitophagy is crucial when treating spinal cord injury, as both excessive and insufficient mitophagy can impede recovery. In this review, we summarize the pathological changes associated with spinal cord injury, the mechanisms of mitophagy, and the direct and indirect relationships between mitophagy and spinal cord injury. We also consider therapeutic approaches that target mitophagy for the treatment of spinal cord injury, including ongoing clinical trials and other innovative therapies, such as use of stem cells, nanomaterials, and small molecule polymers. Finally, we highlight the current challenges facing this field and suggest potential directions for future research. The aim of our review is to provide a theoretical reference for future studies targeting mitophagy in the treatment of spinal cord injury.